Distribution of Diseases, Disease Categories, and Treatment Outcomes among Hospitalized Patients under One Year of Age at the Pediatric Department, Ba Vi General Hospital, 2024-2025 - Thi Tuyet, Le; Ngan, Pham Kim; Nhung, Pham Hong; Huong, Phung Thi Thu; Trang, Pham Thu; Minh, Phung Thi; My, Quach Thi Huyen; Hanh, Vu Thi (VNU Journal of Science: Medical and Pharmaceutical Sciences; Acticle in Press, 2026)
This study was conducted to describe the describe disease patterns, disease categories, and treatment outcomes of inpatients at the Pediatrics Department of Ba Vi General Hospital from June 2024 to May 2025. The study was a retrospective, cross-sectional design based on 2,184 inpatient medical records collected from the hospital management software and classified according to ICD-10. The results showed that male patients accounted for a higher proportion of hospitalizations than female patients (64.1% vs. 35.9%). The highest hospitalization rates occurred during transitional months (March and December). According to ICD-10 classification, respiratory diseases accounted for 61.4%, some diseases arising during the neonatal period (16.7%), digestive diseases 10.57%, and infections and parasitic diseases 3.71%. Pneumonia and gastrointestinal infections were the two most common diseases. The recovery and improvement rate for patients reached 89.79%, and the length of hospital stay (5-10 days) accounted for 46.98%. The research results provide an overview of pediatric disease patterns at the district level, contributing to the orientation of resource allocation, improving the quality of care, and predicting future trends in childhood diseases.